2014
DOI: 10.1016/j.jcol.2014.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological aspects and prevalence of human papillomavirus in anal cancer

Abstract: Anal cancer is relatively rare; however, its incidence has increased in recent years. Several risk factors are associated with the development of anal cancer, including age older than 50 years, low-fiber diet, chronic anal fistulas, smoking, multiple partners, anal intercourse practice, Human Immunodeficiency Virus infection and immunosuppression. However, the presence of human papillomavirus represents the main risk factor for the development of anal cancer. The aim of this study was to evaluate the clinicopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 16 publications
2
9
2
Order By: Relevance
“…Ouhoummanea and co-authors [8] found that the majority of incidence of anal cancer (60%) was in women. Aguiar and colleagues found that 62.8% of patients with anal cancer were women [9]. The results of a study of Czech patients with anal cancer by Tachezy et al [6], in which the same number of patients was analyzed as in our study, revealed that 52.4% of the patients were female.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Ouhoummanea and co-authors [8] found that the majority of incidence of anal cancer (60%) was in women. Aguiar and colleagues found that 62.8% of patients with anal cancer were women [9]. The results of a study of Czech patients with anal cancer by Tachezy et al [6], in which the same number of patients was analyzed as in our study, revealed that 52.4% of the patients were female.…”
Section: Discussionsupporting
confidence: 56%
“…According to several researches, the peak incidence of anal cancer is between the ages of 58 and 64 years [6][7][8][9][10]. The mean age of patients with anal cancer may had vary among studies, possibly because of the type of population studied and the presence of risk factors such as sexual orientation, immunosuppression (patients with HIV+ infection and transplant recipients), tobacco smoking, and alcoholism [6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy allows identifying neoplastic changes at early stages and enables early treatments. Current recommendations indicate anal screening for at-risk groups, including individuals who practice receptive anal sex, people living with HIV/AIDS, and those with a history of anogenital malignancies caused by human papillomavirus (HPV) [20,21].…”
Section: Cytological Examination Used As Screening Strategy For the Ementioning
confidence: 99%
“…According to the Population Based Cancer Registry of Goiânia, between 1989 and 2008, a total of 117 cases of anal cancer were diagnosed in the city, but more recent data were not available. A study carried out in Goiânia, a city in the Midwest region of Brazil, described 42 cases of anal cancer, of which 38 were tested for HPV DNA and 76% were positive for the presence of HPV DNA [12].…”
Section: Introductionmentioning
confidence: 99%